2013
DOI: 10.1371/journal.pone.0067823
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Control by Vitamin D of Granulocytes and Bacteria in the Lungs of Mice: An Ovalbumin-Induced Model of Allergic Airway Disease

Abstract: Vitamin D may be essential for restricting the development and severity of allergic diseases and asthma, but a direct causal link between vitamin D deficiency and asthma has yet to be established. We have developed a ‘low dose’ model of allergic airway disease induced by intraperitoneal injection with ovalbumin (1 µg) and aluminium hydroxide (0.2 mg) in which characteristics of atopic asthma are recapitulated, including airway hyperresponsiveness, antigen-specific immunoglobulin type-E and lung inflammation. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 71 publications
4
42
1
Order By: Relevance
“…The authors went on to investigate whether these effects were dependent on the timing of vitamin D treatment, and found that eosinophil recruitment was inhibited when 1,25(OH) 2 D was administered at a later stage in the exposure protocol. This work is supported by Gorman and colleagues [52] who showed that vitamin D deficiency in a mouse model of OVA exposure suppresses allergic responses in a sex dependent manner. Interestingly, the apparent sensitivity of male mice to the effects of vitamin D deficiency was associated with an increase in bacteria levels in the lung implying a role for vitamin D induced modulation of the microbiome in regulating asthma like responses in the airway.…”
Section: Asthmamentioning
confidence: 53%
“…The authors went on to investigate whether these effects were dependent on the timing of vitamin D treatment, and found that eosinophil recruitment was inhibited when 1,25(OH) 2 D was administered at a later stage in the exposure protocol. This work is supported by Gorman and colleagues [52] who showed that vitamin D deficiency in a mouse model of OVA exposure suppresses allergic responses in a sex dependent manner. Interestingly, the apparent sensitivity of male mice to the effects of vitamin D deficiency was associated with an increase in bacteria levels in the lung implying a role for vitamin D induced modulation of the microbiome in regulating asthma like responses in the airway.…”
Section: Asthmamentioning
confidence: 53%
“…182 An inhibitory effect from 1α,25(OH) 2 D 3 vitamin or calcitriol has been reported also for eosinophils. 102,183 This would highlight the role of vitamin D in asthma. 184,185 In children with asthma, an impaired T-reg population with an altered cytokine spectrum and an increase in CD23 þ CD21 þ -expressing B cells has recently been observed.…”
Section: Role In Acquired and Regulatory Immunitymentioning
confidence: 99%
“…In this study it was not possible to distinguish the effects of maternal vitamin D status versus the role of the vitamin D status of the individual after birth on lung development. 72 A recent publication by our group further explored the mechanisms for explaining the association of vitamin D, lung development and asthma. 73 Previously we investigated the overlap between genes related to vitamin D relative to different DLCGS to infer the role of in utero changes of vitamin D responsive genes in the developing lung and asthma.…”
Section: The Role Of Vitamin D In Fetal Lung Development Genomicsmentioning
confidence: 99%